Comparative analysis of crystallization behavior induced by different mineral fillers in polypropylene nanocomposites - Castillo, Luciana Andrea (2020)
A comparative analysis of crystallization behavior induced by several mineral fillers in polypropylene nanocomposites was performed. Morphological changes and thermal properties of nanocomposites were evaluated, considering the influence of shape, crystalline morphology, and concentration of mineral particles. For this study, hydrated magnesium silicates with different particle morphologies, such as platelets (talc) and fibers (sepiolite), were used for nanocomposites. In addition, to analyze the effect of mineral crystallinity on nanocomposites, talc and sepiolite from different origin and genesis were selected. Nanocomposites were compounded and injection molded, using different filler concentration (0, 1, and 3% w/w) for each mineral particle. To evaluate the particle influence on nanocomposite crystallinity, X-ray diffraction was used to determine crystalline phases and crystal orientation, meanwhile differential scanning calorimetry was performed to obtain thermal properties. Main results revealed that talc has a higher nucleating effect on polypropylene matrix than sepiolite fibers, regardless of their origin and genesis. Meanwhile, a transcrystalline layer that surrounds the fiber surface is observed for nanocomposite containing sepiolite. Moreover, Argentinean talc induces different crystalline phases in nanocomposite with respect to Australian one, which partly influences on mechanical properties.